Efectos jurídicos, sociales y doctrinarios del despojo violento de dominio - César-Arrias, Julio; Macías-Cedeño, Sheila Jazmín (IUSTITIA SOCIALIS, 2021)
Efectos jurídicos, sociales y doctrinarios del despojo violento de dominio